Perawatan Dan Perbaikan Peralatan Listrik Rumah Tangga Bagi Anggota PKBM Ingin Maju Kabupaten Bantaeng - Zulhajji; Muliaty Yantahin; Andi Imran Imran; Haripuddin; Firdaus (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
The main problem in implementing this Community Service activity is how to improve the quality of human resources for members of PKBM Want to Advance Bantaeng Regency in maintaining and repairing household electrical equipment. The aim and benefit of carrying out the activity is to provide basic knowledge for PKBM Want to Advance members on how to maintain and repair household electrical equipment quickly and precisely. The rationale behind this training activity is how to ensure that PKBM Want to Progress Bantaeng Regency members no longer have difficulties in maintaining and repairing household electrical equipment, both PKBM members themselves and in the community. This training is also carried out using lecture, discussion, question and answer and simulation (practice) methods. From these results it can be concluded that the skills of the Bantaeng Regency Want to Advance PKBM members in maintaining and repairing household electrical equipment have increased significantly.